Effects of Leclercia adecarboxylata incorported with agriculture waste materials on growth of cocoa (Theobroma cacao L.) seedlings - Madian, Nurfadzilah (2019)
Cocoa industry in Malaysia has reached the crisis of production where the production and acreage on planting are declining drastically. The total production of cocoa in 2000 was 70,231 tons and continues to decline to 1,723 tons in 2016. This industry has started to decline since 1990's due to the outbreak of disease, unstable price, and relatively high cost of fertilizer. Therefore, Malaysia Cocoa Board is trying hard in minimizing the outbreak of disease and reducing the cost of fertilizer since the major contribution to the cost of production come from the cost of fertilizer. Hence, there is a potential value by emerging the technologies of biofertilizer since the cost production is much cheaper and more environmental friendly. The study was aimed to develop and produce a biofertilizer known as bioenhancer and evaluate the potential value of selected bacteria incorporated with selected carrier materials on the growth response of cocoa seedlings. This study consists of three stages which are isolation and screening of the potential bacteria based on in-vitro and in-vivo studies, viability determination of Leclercia adecarboxylate in the carrier materials and efficacy of bioenhancer in cocoa seedling growth performance. In the first stage, there are 256 isolates (140 of rhizospheric isolates and 116 endophytic isolates) of sixteen healthy cocoa root samples from eight different locations were obtained and further screening was done to identify the most beneficial bacteria with several abilities such as ability to fix nitrogen, solubilize phosphorus and potassium, and ability to produce plant hormone (IAA). This evaluation was done through in-vitro study in Laboratory TG 3 (JTP), Universiti Putra Malaysia and Microbiology laboratory in Cocoa Research and Development Centre, Jengka, Pahang. Further in-vivo study was done in glasshouse nursery at CRDC Jengka to identify highly potential bacteria to be used in the bioenhancer. Seven potential isolates were adopted and based on the result, isolate was identified as Leclercia adecarboxylata. This bacteria shows higher effect on cocoa seedling growth performance. The next stage was evaluation of bacteria viability in the selected carrier materials. The result showed that combination of cocoa pod husk (CPH) and rice husk char (RHC) or single material of rice husk char (RHC) with 1.2% of bacteria solution showed higher colony forming unit after sixth month of applications. The last stage of the study showed that the application of 1.2% of beneficial bacteria with 30 g of CPH and RHC promotes the cocoa seedlings growth rate by 56.05% (plant girth) and 73.15%(plant height) while, applications of 1.2% of beneficial bacteria with 45g of CPH and RHC increase leaves, stem, root weight by 38.66%, 75.35%, and 50.40% respectively as compared with normal chemical fertilizer applications. This result indicated that bacteria incorporated with selected carrier material improve cocoa seedling growth and biomass. The outcome of this study would reduce the cost of production for cocoa plantation and at the same time, helps in utilizing the waste product from agriculture sector.